Genomic characterisation of the metal tolerance protein gene family and elucidation of functional role in heavy metal tolerance and accumulation in Coptis chinensis - Zhang, Yi; Wang, Lili; Zhang, Jinke; Wang, Chenxi; Fan, Yue; Cao, Haohao; Zhang, Huanyu; Ma, Yuchen; Wang, Haoyu; Kang, Jiaxin; Jiao, Yige; Shangguan, Xinxin; et al. (Frontiers in Plant Science, 2025)
Metal tolerance protein (MTP) family members, functioning as plant divalent cation transporters, play essential roles in maintaining heavy metal homeostasis and tolerance. This study presents a novel comprehensive genomic characterisation of the MTP gene family in Coptis chinensis, involving systematic identification and functional annotation. A total of 25 CcMTP genes were identified and classified into three major subfamilies based on phylogenetic analysis. Conserved motif profiling and gene structure annotation revealed both conserved and divergent features among the subfamilies. Genomic collinearity analysis identified one tandemly duplicated gene pair (CcMTP12/CcMTP20) in C. chinensis. The promoter regions of CcMTP genes were enriched with cis-acting elements associated with phytohormones, light, and growth and development. Gene expression analysis showed that several CcMTPs were significantly upregulated in response to cadmium stress across different tissues. CcMTP11, CcMTP16, and CcMTP24, which exhibited high expression in roots, stems, and leaves, conferred enhanced tolerance to multiple heavy metals. Notably, CcMTP24 promoted Δycf1 yeast growth under Cd, iron, zinc, and manganese stress and reduced Cd accumulation in yeast. Collectively, pivotal CcMTPs, such as CcMTP24 identified in this study, may provide mechanistic insights to elucidate the roles of MTPs in heavy metal tolerance in C. chinensis.